Junk DNA A Journey Through the Dark Matter of the Genome - Carey, Nessa (Columbia University Press, 2015)
For decades after identifying the structure of DNA, scientists focused only on genes, the regions of the genome that contain codes for the production of proteins. Other regions that make up 98% of the human genome were dismissed as junk," sequences that serve no purpose. Yet recently researchers have discovered variations and modulations in this junk DNA that underwrite a number of intractable diseases. This knowledge has led to innovative research and treatment approaches that may finally control these conditions.Junk DNA can play vital and unanticipated roles in the control of gene expression, from fine-tuning individual genes to switching off entire chromosomes. Its function has forced scientists to revisit the very meaning of the word gene" and has engendered a bitter battle over whether or not this genomic nonsense" is the source of human biological complexity. Drawing on her experience with leading investigators in Europe and North America, Nessa Carey provides a clear and compelling introduction to junk DNA and its critical involvement in phenomena as diverse as genetic diseases, viral infections, sex determination in mammals, disease treatments, and evolution. We are only now unlocking the secrets of junk DNA, and Carey's book is an indispensable resource for navigating the codes and controversies of this fast-growing and hotly disputed field